2013
DOI: 10.1109/lpt.2013.2278973
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Optical Fiber Refractive Index Sensor Employing an In-Line Submillimeter Hole

Abstract: An in-line submillimeter hole fabricated by microdrilling plastic optical fiber (POF) directly has been proposed as a compact refractive index sensor. Since the hole behaves as a concave lens if it is filled with a liquid having lower refractive index than that of the fiber core, transmittance increases in proportion to the refractive index. Analysis of the sensor transmittance has been performed using a simple ray optics model. Through immersing a 1.5-mm POF with a 0.35-mm-radius hole into various liquids, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 10 publications
2
28
0
Order By: Relevance
“…Refractive index (RI) sensors are very important for monitoring water quality in either industrial applications or environmental control [1,2]. Many RI sensor configurations using optical fibers technology have been studied in the last years such as multimode tapered fibers [3], fiber-taper seeded long period grating (LPG) pair [4], multimode interference (MMI) devices [5], structures based in core diameter mismatches [6], Michelson interferometer using abrupt taper [7], core offset attenuators [8], in-line Mach-Zehnder interferometer setup by concatenating two singlemode fiber (SMF) tapers [9], and MMI based tapered fiber [10]. Most of those sensor configurations offer high sensitivity for RI close to 1.45 (RI of the fiber cladding), but present a relatively low sensitivity for RI close to distilled water ($1.333), a range of interest for many chemical and biosensing applications.…”
mentioning
confidence: 99%
“…Refractive index (RI) sensors are very important for monitoring water quality in either industrial applications or environmental control [1,2]. Many RI sensor configurations using optical fibers technology have been studied in the last years such as multimode tapered fibers [3], fiber-taper seeded long period grating (LPG) pair [4], multimode interference (MMI) devices [5], structures based in core diameter mismatches [6], Michelson interferometer using abrupt taper [7], core offset attenuators [8], in-line Mach-Zehnder interferometer setup by concatenating two singlemode fiber (SMF) tapers [9], and MMI based tapered fiber [10]. Most of those sensor configurations offer high sensitivity for RI close to 1.45 (RI of the fiber cladding), but present a relatively low sensitivity for RI close to distilled water ($1.333), a range of interest for many chemical and biosensing applications.…”
mentioning
confidence: 99%
“…When fabricating the POF respiration sensor, multiple in-fiber microholes were first created in the central part of the POF using an inexpensive drilling machine. [15][16][17] Next, the waist-band was created by stitching elastic fabric to each side of an inelastic fabric centerpiece. The central part of the POF was then embedded in the inelastic fabric, while the remaining parts were merged into the elastic fabric on each side.…”
Section: Sensor Fabrication and Experimental Resultsmentioning
confidence: 99%
“…Figure shows a schematic diagram of a POF with a single in‐fiber microhole. When the POF is unbent (Figure A), the transmittance of the POF with a single hole is given as normalT=false[cos1()n2n1sin1()rhL+tan1()rhsinθh,maxLrhcosθh,maxcos1()n2n1, where n 1 and n 2 are the core and cladding refractive indices, respectively, r h is the hole radius, θcfalse(=sin1n2n1) is the critical angle, L = atan θ c , and θ h , max is the maximum angle between the fiber axis and the point where the traversing ray reaches the microhole. Thus, if the POF has N in‐fiber microholes along its axis, the transmittance becomes T N = T N .…”
Section: Introductionmentioning
confidence: 99%
“…[16], [17]. Shin J, et al [18] and Xin G, et al [19] both reported a micro-hole based POF sensor, experimentally showing its feasibility for RI testing.…”
mentioning
confidence: 99%